2008
DOI: 10.3354/ame01195
|View full text |Cite
|
Sign up to set email alerts
|

Algal bioactive compounds reduce net oxygen fluxes of artificial diatom biofilms

Abstract: A wide range of chemicals are exuded by microalgae or released by grazed cells. In biofilms, these bioactive compounds may potentially exert a large effect on growing cells, since the cellular density is high and intercellular distances are short. We studied whether such compounds affect the functioning of the biofilm and, therefore, we tested several compounds. These included eicosapentaenoic acid (EPA) and 2E, 4E-decadienal (DD), which are produced during grazing on diatoms. In addition, we obtained a mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This may be counteracted by the fact that PUAs are directly produced inside the digestive tract of grazers (Wichard et al, 2008). Interestingly, although data on freshwater micro-algae are scarce, they seem to be less sensitive to PUAs than do marine micro-algae (Adolph et al, 2004;Leflaive et al, 2008). For all the phototrophic organisms tested, the observed effects of PUAs were similar to apoptosis, as described for animals (Ianora et al, 2004;Poulet et al, 2007a).…”
Section: Allelopathic Activity Of Puas and Pufasinteractions Between mentioning
confidence: 83%
See 1 more Smart Citation
“…This may be counteracted by the fact that PUAs are directly produced inside the digestive tract of grazers (Wichard et al, 2008). Interestingly, although data on freshwater micro-algae are scarce, they seem to be less sensitive to PUAs than do marine micro-algae (Adolph et al, 2004;Leflaive et al, 2008). For all the phototrophic organisms tested, the observed effects of PUAs were similar to apoptosis, as described for animals (Ianora et al, 2004;Poulet et al, 2007a).…”
Section: Allelopathic Activity Of Puas and Pufasinteractions Between mentioning
confidence: 83%
“…Interestingly, although data on freshwater micro‐algae are scarce, they seem to be less sensitive to PUAs than do marine micro‐algae (Adolph et al. , 2004; Leflaive et al. , 2008).…”
Section: Allelopathic Activity Of Puas and Pufas – Interactions Betwementioning
confidence: 99%
“…Interspecific chemical interactions in diatoms have been poorly studied despite their diversity and abundance in all aquatic habitats. However, recent studies have revealed that allelochemicals from benthic diatoms are diverse: eicosapentaenoic acid, a polyunsatured fatty acid and 2E,4E-decadienal, a polyunsaturated aldehyde (Leflaive et al 2008a;Leflaive and Ten-Hage, 2009), polyphenolic compounds (Pouvreau et al, 2007), cyanogen bromide (BrCN) a halogenated compound (Vanelslander et al, 2012). All these compounds are produced by benthic diatoms and target co-occurring benthic diatoms.…”
Section: High Diversity Of Reported Allelopathic Interactionsmentioning
confidence: 99%
“…Colony formation was expected to provoke higher sedimentation rates (Lürling and Van Donk 2000) and thus lower shading effects. These extracts could also inhibit or decrease the growth and the photosynthetic activity of benthic/epiphytic algae, such as the diatom Nitzschia palea (Leflaive et al 2008b;Leflaive and Ten-Hage 2009). The production of allelopathic compounds by U. confervicolum was controlled by intrinsic (growth phase) and extrinsic (light, nutrients) factors.…”
Section: Introductionmentioning
confidence: 98%